Application and potential of electrical stimulation - Curtis L. Kastner (Kansas Agricultural Experiment Station Research Reports, 1980)
It has been known for years that electrical stimulation will improve tenderness of meat, but the technique only recently has gained considerable interest in the meat industry. Benjamin Franklin in 1749 observed that killing turkeys electrically made the muscle quite tender. In 1951, Harsham and Deatherage and Rentschler gained separate patents for tenderizing carcasses with electrical stimulation. Tenderness was the most obvious change stemming from electrical stimulation. However, research efforts in New Zealand, England, and the United States have recently attributed other important results to the technique.
Keywords: Cattlemen' s Day; 1980; Report of progress (Kansas State University. Agricultural Experiment Station); 377; Beef; Electrical stimulation; Tenderness